Of Shastric ‘Yogams’ and polyherbals - Naraindas, Harish (Asian medicine, 2014)
This is an essay on the formulary logic of contemporary ayurvedic drugs. It suggests that there are three different ways of conceiving this logic: the biomedical formulary, the polyherbal formulary of the West, and the ayurvedic formulary. The ayurvedic formulary has a long history of endogenous innovation. Its epistemic logic is best understood through the language of a shastric yogam. This paper will attempt to look at what this logic entails and how it is being transformed by contemporary drug making practices. The transformation produces a range of therapeutic possibilities that bears comparison with and resembles, however, not the biomedical but the polyherbal formulary of the contemporary West. This results neither in a straightforward ‘biomedicalisation’ nor in a ‘herbalisation’ of Ayurveda but leads instead, through a mangling of epistemic registers, to its creolisation and the production of a new ‘formulary language’ which is carefully and critically addressed.